2023
DOI: 10.1186/s12915-023-01562-w
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association reveals host-specific genomic traits in Escherichia coli

Abstract: Background Escherichia coli is an opportunistic pathogen which colonizes various host species. However, to what extent genetic lineages of E. coli are adapted or restricted to specific hosts and the genomic determinants of such adaptation or restriction is poorly understood. Results We randomly sampled E. coli isolates from four countries (Germany, UK, Spain, and Vietnam), obtained from five host species (human, pig, cattle, chicken, and wild boar)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 80 publications
1
6
0
Order By: Relevance
“…The predominant bacterial phyla in the caecal mucosal epithelium samples were Firmicutes , Actinobacteria , Proteobacteria and Bacteroidota , which is consistent with previous studies of swine caecal microbiomes [9, 19, 40]. Escherichia coli was the predominant pathogen found in the caecal microbiome, which is a common pathogen in both humans and animals [41–43]. This pathogen is associated with post-weaning diarrhoea and oedema disease in swine, which can have an enormous economic impact.…”
Section: Discussionsupporting
confidence: 85%
“…The predominant bacterial phyla in the caecal mucosal epithelium samples were Firmicutes , Actinobacteria , Proteobacteria and Bacteroidota , which is consistent with previous studies of swine caecal microbiomes [9, 19, 40]. Escherichia coli was the predominant pathogen found in the caecal microbiome, which is a common pathogen in both humans and animals [41–43]. This pathogen is associated with post-weaning diarrhoea and oedema disease in swine, which can have an enormous economic impact.…”
Section: Discussionsupporting
confidence: 85%
“…The most prevalent lineage in our dataset was the ST10 clone, a well-known high-risk pandemic lineage associated with infections in humans and has been found in livestock and meat in Peru ( 43 , 44 ) Other STs identified in this study, such as ST117, have been found in emerging ExPEC strains of foodborne E. coli , posing a risk to human health ( 45 , 46 ). ST752 has been associated with poultry in Europe and the United States and is considered predominant in chicken populations ( 47 , 48 ). ST7176 has been detected in porcine E. coli strains carrying the bla CTX-M-55 variant ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…MDR traits can spread from contaminated animal products to humans or be introduced directly into the natural environment through fecal matter [ 13 , 14 ]. E. coli has become a repository of antibiotic-resistant genes, making it a key indicator for monitoring the prevalence of antibiotic resistance, a role recognized by the World Organization for Animal Health (OIE) [ 2 , 15 , 16 ]. In addition, E. coli also has the ability to transfer genes to other bacterial species, including pathogens [ 15 ].…”
Section: Introductionmentioning
confidence: 99%